Ace school

with brainly

  • Get help from millions of students
  • Learn from experts with step-by-step explanations
  • Level-up by helping others

A community for students.

Part 1: Explain, in complete sentences, which method you would use to solve the following system of equations. (1 point) Part 2: Explain why you chose that method (1 point) Part 3: Provide the solution to the system. (2 points) x – 3y + 2z = –12 x + 2y + 3z = 6 2x – 3y – z = –2

Mathematics
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Join Brainly to access

this expert answer

SEE EXPERT ANSWER

To see the expert answer you'll need to create a free account at Brainly

What math are you taking?
Algebra 2
Yeah i don't know. I would say substitution.

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

well, I've got how to with two equations, just cant remember how to do three.
Having trouble, cuz if you can just tell me what do do, you dont have to give me the answer, I'll just figure it out
such question is a system of linear equation for further mathematics....so we can reduce it to triangular system and use back substitution...........gaussian elimination would also be appropriate.....or use matrix format with row reduction appplication...actually i am doing an assignment on it
the y is because we have 3 equations with 3 unknowns in it.so the given methods will be right
Bro, i have no idea what you just said..
no bro but sis......i`ll give u the steps....you follow then do it....ok
Yeah I would say substitution too. Solving the first equation for x in terms of y and z yields, x=3y-2z-12. Substituting the value of x in the second and third equations yields a system of two equations in two unknowns: (3y-2z-12)+2y+3z=6 2(3y-2z-12)-3y-z=-2 => 3y-2z-12+2y+3z=6 6y-4z-24-3y-z=-2 => 5y+z=18 3y-5z=22 for z gives, z=-5y+18 substituting the value of z in the second equation gives: 3y-5(-5y+18)=22 3y+25y-90=22 28y=112 y=4 substituting the value of y in the first equation: 5(4)+z=18 20+z=18 z=-2 substituting the value of y and z in the value of x that we first got ^^ : x=3y-2z-12 x=3(4)-2(-2)-12 x=12+4-12 x=4 The solution set is: { (4,-2,4) }
Thank you soo much!
You're welcome!

Not the answer you are looking for?

Search for more explanations.

Ask your own question